An Information Operational Model for Tourism Management in Thai Supply Chain - Artaphon Chansamut (ExcelingTech, 2023)
The purpose of this research were to develop an information operational model for tourism management in Thai supply chain and to assess an information operational model for tourism management in Thai supply chain. The research methodology was divided into three step namely study researches relevant to the elements of an information operational model for tourism management in Thai supply chain and developing the examined in terms of its quality by ten expert include data were analysed by mean, standard deviation .The research found there were five type of an information operational model for tourism management in Thai supply chain namely Main element , Suppliers, Tours Operator, Agents and Customers. The results from experts have evaluated the model is high level of appropriateness and can develop information system the tasks.